(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Devoted to the study of the use of neurolinguistic programming (NLP) for motivation in the process of teaching Russian as a foreign language. Exploring the use of NLP to improve learning effectiveness. The theoretical foundations of NLP are reviewed, including its history, principles and impact on the development of communication skills